PERBANDINGAN KANDUNGAN MINYAK ATSIRI TANAMAN SEREH WANGI (Cymbopogon nardus L. Rendle) YANG DITANAM DI LOKASI BERBEDA - Dacosta, Margareta; Sudirga, Sang Ketut; Muksin, I Ketut (SIMBIOSIS, 2017)
It has been conducted a research that aims to determine the ratio of essential oil content of citronella stalks ( Cymbopogon nardus Rendle L. ) grown in the lowlands of Denpasar and the highlands of Bedugul. The experiment was conducted by using experimental designs. The parameters measured were the volume and the level of citronella oil produced. The sample preparation of powdered citronella stalks was as much as 200 grams, macerated with 96% ethanol and evaporated with Vacuum rotary evaporator to form condensed extract. The research used quantitative methods. The volume of hydro distillation was to obtain a crude extract of citronella stalks and the identification of active compounds was conducted by using Gas Chromatography / Mass Spectrometry (GC-MS). It can be concluded that the levels of citronella essential oil stalks from the highland of Bedugul was higher than the lowland areas of Denpasar, while the quality of essential oil of the lowland of Denpasar was better than that of the Bedugul highland. The content of secondary metabolites of the results of GC-MS analysis obtained from the essential oils contained in the analyzed crude extract of citronella stalks namely the compound of Selina-6-en-4-ol (2287322), the compound of n-hexadecanoic acid (1238019) and the compound of Driman-8,11-diol from the lowland of Denpasar while the Selina compound-6-en-4-ol (1856137) from the highland of Bedugul. Keywords: Citronella, essential oil content, altitude